Respuestas

¡La mejor respuesta!
2012-06-10T04:30:29+02:00

∫ (secx)^3 dx = ∫ secx (secx)^2 dx
∫ (secx)^3 dx = ∫ secx [ (tanx)^2 + 1] dx
∫ (secx)^3 dx = ∫ secx (tanx)^2 dx + ∫ secx dx

para integrar : ∫ secx (tanx)^2 dx
por la formula de integracion por partes:
∫ UdV = UV - ∫ Vdu
tomando:
U = tan x .......................dV = secx tanx
dU = (secx)^2 .............. V = secx

por lo tanto tenemos:

∫ (secx)^3 dx = tanx secx - ∫ (secx)^3 + ∫ secx dx
∫ (secx)^3 dx + ∫ (secx)^3 = tanx secx + ∫ secx dx
2 ∫ (secx)^3 dx = tanx secx + ln (secx + tanx) + c
∫ (secx)^3 dx = 1/2 [ tanx secx + ln (secx + tanx) ] + c